Antibacterial TAP-mimic electrospun polymer scaffold: effects on P. gingivalis-infected dentin biofilm - Albuquerque, Maria Tereza P. [UNESP]; Evans, Joshua D.; Gregory, Richard L.; Valera, Marcia C. [UNESP]; Bottino, Marco C. (Springer, 2016)
Objectives This study sought to investigate, in vitro, the effects of a recently developed triple antibiotic paste (TAP)mimic polymer nanofibrous scaffold against Porphyromonas gingivalis-infected dentin biofilm. Materials and methods Dentin specimens (4 x 4 x 1 mm(3)) were prepared from human canines. The specimens were sterilized, inoculated with P. gingivalis (ATCC 33277), and incubated for 1 week to allow for biofilm formation. Infected dentin specimens were exposed for 3 days to the following treatments: antibiotic-free polydioxanone scaffold (PDS, control), PDS + 25 wt% TAP 25 mg of each antibiotic (metronidazole, ciprofloxacin, and minocycline) per mL of the PDS polymer solution], or a saturated TAP-based solution (50 mg of each antibiotic per mL of saline solution). In order to serve as the negative control, infected dentin specimens were left untreated (bacteria only). To determine the antimicrobial efficacy of the TAP-mimic scaffold, a colony-forming unit (CFU) per milliliter (n = 10/group) measurement was performed. Furthermore, additional specimens (n = 2/group) were prepared to qualitatively study biofilm inhibition via scanning electron microscopy (SEM). Statistics were performed, and significance was set at the 5 % level. Results Both the TAP-mimic scaffold and the positive control (TAP solution) led to complete bacterial elimination, differing statistically (p < 0.05) from the negative control group (bacteria only). No statistical differences were observed for CFU per milliliter data between antibiotic-free scaffolds (2.7 log(10) CFU/mL) and the negative control (5.9 log10 CFU/mL). Conclusions The obtained data revealed significant antimicrobial properties of the novel PDS-based TAP-mimic scaffold against an established P. gingivalis-infected dentin biofilm. Clinical relevance Collectively, the data suggest that the proposed nanofibrous scaffold might be used as an alternative to the advocated clinical gold standard (i.e., TAP) for intracanal disinfection prior to regenerative endodontics.
Keywords: Electrospinning; Scaffold; Antibiotic; Disinfection; Endodontics; Nanofibers